Manifestation of the Need to Realize One’s Abilities Working for the Sake of Others in Akmenė District Elderships - Liukinevičienė, Laima; Statkuvienė, Rasa (Socialiniai tyrimai, 2018)
The works of Lithuanian scientists who have been analyzing human resource management issues in the context of public administration during the last decade show that human resource management processes in public sector institutions lack integrity with the strategic management of the entire organization, and that municipalities lack the experience in creating influential employee motivation systems as well as the experience in choosing the employees who have not only high professional competencies, but are also motivated to work selflessly for the sake of others. This is particularly relevant today as the decentralization of management is increasing (there are more than 3000 elderships and over 800 rural communities in Lithuania), and more and more functions are being transferred to municipalities. A part of the challenges facing the management sector has to be taken over by the elderships that possess a limited budget and a small number of employees (usually, there are up to 10 employees: 1–2 civil servants and the rest are contract staff). In these administrative structures, the inner motivation of employees and the inner need to implement their own skills working for the sake of the community and society in general, i.e. the self-transcendence (according to the English terminology), often facilitate to attain the goals of the organization creatively, innovatively, and with a great responsibility. Having penetrated into the theoretical conception of self-transcendence as the concept of motivation and the inner needs of an employee, and following the actualization of this phenomenon in the state service in order to validate the empirical analysis of the self-transcendence practice and significance in the eldership as well as to ground the construction of research instruments, the following theoretical perspectives were chosen: the integration of theory of needs with other theories of self-expression, by Maslow, and self-transcendence as the actualization of an individual’s self-realization top need in the context of the state service, according to Vanagas and Rakšnis, 2014; the concept of a leader as a Self-Leading Leader, by Henry J. Venter, 2012; the need for self-realization in the public service, according to J. Palidauskaitė, 2008; community-level leadership as the essential condition for the functioning of local self-governance, by Urvikis, 2016, and others. Analysis of the theoretical sources testifies that there is still a lack of scientific works analyzing self-transcendence not only as an individual’s need to work selflessly for the sake of others, realizing his / her abilities, and thus improving oneself, but also as a desirable organizational quality of a public sector bringing the employees’ aspirations closer to the mission of the organization (in order to meet public expectations). It can also be stated that the Lithuanian language would require a more appropriate term – a Lithuanian word – as an equivalent to the international term ‘Self-transcendence’ that would describe the motive of a civil servant to work for the sake of others, i.e. the motive arising from the inner need for self-realization. Akmenė district was chosen as the research area. The study was carried out focusing on the elderships functioning in the district due to the fact that in 2015–2016 this rural municipality of Northern Lithuania, on the one hand, had quite a lot of unemployment, and on the other hand, it distinguished itself by the abundance of initiatives and wise activities applied to solve social problems. In 2016, V. Mitrofanov, the Mayor of the District, was elected Mayor of the Year. This empirical research was based on the strategy of hybrid methods usage where the quantitative and qualitative research methods were combined. Research was carried out in all the elderships of Akmenė district, and its results testified quite a favourable situation for the employees’ need to realize their abilities by working for the sake of others or, in other words, the results testified quite a favourable atmosphere to develop the need for self-transcendence: According to the results of the general survey of employees, in the context of a relatively high level of employee satisfaction in their work (in a ten-point scale, 80% of the respondents rated their work by 7–10 points), the employees of the elderships identified the possibility of self-realization among the important factors (4.1 out of 5 points possible). Manifestation of the self-transcendence motives was also strong (3.8–4.28 points). The eldership employees, in addition to the material motivation measures, also actualized the non-material motivation measures (importance of the material measures was assessed by 9.08 points, and the non-material ones were assessed by 8.53 points out of 10 points possible). 8.75 points were assigned to the motivating factor of self-transcendence, primarily functioning as activities to satisfy the needs of the others. The leaders of the elderships were aware of the fact (the interview method of discussion was used) that the financial incentives were the most influential measures in motivating the employees, however, due to the absence of funding, a large variety of non-material motivational measures, mostly organizational and psychological, were used. Both the questionnaire surveys and the material of the discussion of the elders confirmed the importance of each elder’s leadership in orienting the team to work for the sake of the community. The elders applied such non-material motivation measures, functioning as motivation measures for self-transcendence, as the involvement of employees in decision-making, teamwork, and cooperation with communities. Eldership leaders perceived the external factors supporting the self-transcendence (recognition of an altruistic activity and its support by the public as well as the perception of its phenomenal value in the society) and the internal factors (the elder’s exemplary behaviour; relationship of the activity results of the eldership with the welfare of the employees and the community; publicity of altruistic activities) supporting the self-transcendence in the elderships. They also identified the factors undermining this phenomenon, such as a demotivating and negative attitude of the society towards municipal employees, and the lack of competencies to improve self-transcendence in the civil service. This empirical research has concluded that there is still no systematic perception of such a specific feature of an employee as the desire to work for the others’ sake in an unselfish manner in all the processes related to human resource management (in the selection of employees, assessment of the employees’ qualifications, their motivation and promotion, etc.) either in the rural elderships, or in the municipal administrations. Therefore, the topics of human resource management remain relevant dealing with public sector institutions.